Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
OCLC: 26767689
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Manifest Manners: Narratives on Postindian Survivance - Vizenor, Gerald Robert (Univ. of Nebraska Press, 2010)
Combines post-modern theory with the comic wisdom of the tribal trickster to explore the effects of nostalgic simulations of "Indian-ness".
OCLC: 837681052
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Talking Back to the West: Contemporary First Nations Artists and Strategies of Counter-appropriation - Froschauer, Christina Marie (Concordia University, 2011)
Over a twenty-year period, renowned artists such as Edward Poitras, Robert Houle, Jim Logan, Kent Monkman, among others, appropriate renowned colonial landscape paintings and art historical canonical works, and then alter them to include First Nations narratives, as methods of critiquing the exclusionary nature of grand colonial narratives and their associated historical, art historical and, by extension, anthropological discourses. Using counter-appropriation as an artistic strategy, they critique: the West's disregard for First Nations histories in North America; Art History's past failures to classify their art objects as Fine Art; and contemporary cultural constructions of "Indianness" originating from colonial history and ideologies about the "Vanishing Race." With their works, the artists offer their viewers insight into First Nations histories and stories, thereby enriching the multiple narratives and pluralist discourses existent in North America.
OCLC: 896966575
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Digital Identity: The Construction of Virtual Selfhood in the Indigenous Peoples' Movement - Niezen, Ronald (Comparative Studies in Society and History, 2005)
Inventions have their greatest impact when they go beyond their possible practical applications and act upon the imagination. When Martin Behaim invented the first globe in 1490, a functionally useless object consisting mostly of terra incognita, he was widely ridiculed; but somehow the ideas that his globe represented stuck, and within a few decades the basic validity of his construction was confirmed by the voyages of Columbus, Cabot, Vasco de Gama, Magellan, and others. Today, with efforts to situate the rapid growth of information and communication technologies (ICTs), especially the Internet, in the context of globalization, there is a similar division between those who dismiss it as being of no importance and those who see in it a looming (for good or ill) global revolution. But, as with Behaim's globe, the imaginary possibilities of these innovations are important in determining how and to what extent human existence is to be transformed by them
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Indigenous Aestetics: Native Art, Media and Identity - Leuthold, Steven M.... (University of Texas Press, 1998)
What happens when a Native or indigenous person turns a video camera on his or her own culture? Are the resulting images different from what a Westernized filmmaker would create, and, if so, in what ways? This book discusses the core concepts of aesthetics and indigenous culture and examines the work of American Indian documentary filmmakers
Section: XIII-238 p. : illustrations ; 24 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La "chose indienne": cinéma et politiques de la représentation autochtone au Québec et au Canada - Cornellier, Bruno (Nota bene, 2015)
Comment se fait-il que le Canada puisse être représenté par des totems indiens à Walt Disney World ou par un inukshuk aux Jeux olympiques de Vancouver ? Il y a indéniablement « quelque chose » d’indien à propos du Canada. Pour survivre moralement et politiquement à son héritage colonial, l’État a besoin de se faire lui-même partiellement indien. Il lui faut ce je-ne-sais-quoi, cette « chose indienne », nommée sans l’être complètement, signalée sans jamais être définie. Cette indianité, bien qu’elle soit interpellée par la présence d’Autochtones, n’a plus besoin d’eux pour se manifester en tant que réalité. Historiquement, le cinéma constitue l’un des lieux privilégiés où se manifeste cette « chose indienne » prise dans les rets de l’imagination libérale et coloniale qui alimente les velléités de souveraineté du Québec et du Canada. Dans la mesure où une telle capture constitue l’un des principaux exercices politiques de l’État, le présent ouvrage avance une conception de la décolonisation qui ne relève plus de la révélation d’une réalité de l’Indien, cachée derrière sa représentation et ses distorsions filmiques, prête à resurgir au profit d’une « reconnaissance » par et dans l’État souverain. Il s’agit plutôt de comprendre le rapport colonial comme une lutte multipartite entre Canadiens, Québécois et Autochtones, avec pour enjeu de s’emparer du pouvoir exclusif de désigner et de représenter ce (et ceux) que cette « chose indienne » pourra (ou non) signifier et autoriser dans le voisinage colonial du souverain.
Section: 310 pages : illustrations ; 21 cm
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé; _À vérifier-Cinéma